CARMA3: Scaffold Protein Involved in NF-κB Signaling - Zhang, Shilei; Lin, Xin (Frontiers in Immunology, 2019)
Scaffold proteins are defined as pivotal molecules that connect upstream receptors to specific effector molecules. Caspase recruitment domain protein 10 (CARD10) gene encodes a scaffold protein CARMA3, belongs to the family of CARD and membrane-associated guanylate kinase-like protein (CARMA). During the past decade, investigating the function of CARMA3 has revealed that it forms a complex with BCL10 and MALT1 to mediate different receptors-dependent signaling, including GPCR and EGFR, leading to activation of the transcription factor NF-κB. More recently, CARMA3 and its partners are also reported to be involved in antiviral innate immune response and DNA damage response. In this review, we summarize the biology of CARMA3 in multiple receptor-induced NF-κB signaling. Especially, we focus on discussing the function of CARMA3 in regulating NF-κB activation and antiviral IFN signaling in the context of recent progress in the field.